Effect of Laser Radiation on Optical Properties of CdO Thin Films - Wadi, Hala abd (Journal of Science and Technology, 2017)
CdO thin films were prepared by chemical spray pyrolysis technique. The study of laser radiation was held in this research in order to estimate the influence of laser on the optical parameters of CdO thin films. The transmittance was increased after laser radiation in comparison with its values before irradiation. While the absorbance shows a trend of increasing in the low wavelength region and increasing in the high wavelength region. The value of the optical energy gap was increased after irradiation. All the rest optical constants under investigation were affected by laser radiation showing decrement on their values.